Effects of corn particle size on broiler performance during the starter, grower, and finisher periods - A.A. Rubio; J.B. Hess; W.D. Berry; W.A. Dozier, III; W.J. Pacheco (Journal of Applied Poultry Research, 2020)
Summary: A considerable segment of the broiler industry in the US grinds corn to approximately 800 μm regardless of the production period of broilers. However, research evaluating optimum corn particle size during each production period is sparse. Therefore, 3 experiments were conducted to determine the effect of corn particle size on growth performance of broilers during the starter, grower, and finisher periods. The experiments consisted of 4 dietary treatments in which broilers received different corn particle sizes depending on the feeding phase: 674, 741, 805, and 912 μm in the starter period from 1 to 14 D of age (experiment 1); 629, 763, 814, and 1,779 μm in the grower period from 14 to 28 D of age (experiment 2); and 615, 863, 1,644, and 2,613 μm in the finisher period from 28 to 42 D of age (experiment 3). In experiments 1 and 2, corn particle size did not influence BW, feed intake (FI), and FCR. In experiment 3, FI increased when broilers were fed with diets containing a corn particle size of 1,644 μm compared with broilers fed with diets containing a corn particle size of 615 μm. However, feeding diets with a corn particle size >1,644 μm increased FCR at 42 D. These data indicated that diets with a corn particle size of 912 and 1,779 μm did not influence growth performance during the starter and grower periods, respectively. However, a corn particle size >1,644 μm can negatively influence FCR during the finisher period from 28 to 42 D of age.